TRANSFORMASI PENDIDIKAN PESANTREN DI ERA MODERN : ANTARA TRADISI DAN INOVASI - Harmathilda Harmathilda; Arief Rahman Hakim; Damayanti Damayanti; Cecep Supriyadi (Universitas Islam Depok, 2024)
The transformation of Islamic boarding school education in Indonesia in the modern era is a complex phenomenon involving tradition and innovation. Islamic boarding schools, as traditional Islamic educational institutions, have the challenge of adapting to rapid developments. This is due to efforts to maintain traditional values ​​while integrating innovation values ​​as the essence of this transformation. This research aims to explain the transformation of Islamic boarding school education, describing the role of tradition and innovation, as well as the challenges and opportunities in aligning these two transformation paradigms. Researchers used qualitative research, with literature study and field study research techniques. The research results show that the transformation of Islamic boarding school education requires a balance between maintaining traditional identity and adopting innovative values, which are related to current educational needs. Education stakeholders must have knowledge about educational transformation, especially when they want to design Islamic boarding school education strategies that are responsive to social, cultural and technological changes.